PEMETAAN PERMASALAHAN POTENSI PENGEMBANGAN DAN IMPLEMENTASI KTSP PENDIDIKAN DASAR DI KOTA MATARAM - Mumbrita Sulaimi (Jurnal Kependidikan, 2010)
This study aims to: (1) to map the problems in the development and implementation of KTSP on basic education units (SD / MI and SMP / MTs) in Mataram, (2) map the resource potential of Mataram city that supports the development and implementation of educational level KTSP bottom. Methodologically, this research conducted eclectic involving teachers and principals as the main subject and the students, supervisors, school committees, and curriculum developers as an informant. The selection of research subjects using the technique of stratified cluster sampling quotas. Data collected by questionnaire, the study documents, and Focus Group Discussion (FGD) to obtain quantitative and qualitative data. Overall the data are analyzed quantitatively (simple percentages and tables) and qualitatively through the three stages of data reduction, data display, and conclusion drawing / verification. The results showed: (1) Problems in developing and implementing KTSP the level of Primary Education in the City of Mataram is not KTSP development refers to the potential and characteristics of schools and the Vision, Mission, and school goals; choice of subjects is very limited local content, and teachers' difficulties implement active learning and innovative. (2) potential to be developed and implemented as local content Mulok subjects in primary education level in the city of Mataram is the potential socio-cultural and natural wealth Lombok area, production and packaging skills of a local specialty, skills and crafts typical of the area Lombok, Lombok history , regional dances, folk music and art